Penerapan Behavior Tree untuk Pengambilan Keputusan Non-Player Character pada Gim Balap - Fitraldy Soefana; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Video Game is an electronic game that involves a joystick, keyboard and motion detector as an input device or user interface to generate feedback for the player which is displayed visually through televisions, monitors and other visual media. Of the many genres, racing games are one that is popular and played by many people, in the Racing game there are characters that cannot be controlled by the player, namely the Non-Player Character (NPC) who acts as an enemy or ally in the game. This NPC will be designed and implemented using the Behavior Tree method, the first thing to do is look at the behavior of the NPC then design the Node to implement the Behavior Tree on the NPC in decision making. After the NPC is implemented, then testing is carried out on the NPC, testing is carried out using the Black Box method, and testing the performance of the NPC, on the Black Box test based on the Test Flow Diagram and testing the performance of the NPC based on Frames per Second and the number of collisions on the NPC. From the results of the Black Box test carried out, the NPC's behavior went as expected, and in testing the performance of the NPC, the resulting game was able to run on average at 60 FPS and on the number of collisions on NPCs the more NPCs resulted in a lot of collisions too so it could be concluded that the game can run at a good FPS and the ability of NPCs to make decisions in large numbers is increasingly difficult.